2018
DOI: 10.1186/s12864-018-5019-9
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome of streamlined marine actinobacterium Pontimonas salivibrio strain CL-TW6T adapted to coastal planktonic lifestyle

Abstract: BackgroundPontimonas salivibrio strain CL-TW6T (=KCCM 90105 = JCM18206) was characterized as the type strain of a new genus within the Actinobacterial family Microbacteriaceae. It was isolated from a coastal marine environment in which members of Microbactericeae have not been previously characterized.ResultsThe genome of P. salivibrio CL-TW6T was a single chromosome of 1,760,810 bp. Genomes of this small size are typically found in bacteria growing slowly in oligotrophic zones and said to be streamlined. Phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 105 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…This genus includes only one species ( P. salivibrio ) and the only cultivable strain (CL-TW6) was isolated in Korea from a solar saltern pond showing salinity slightly higher than seawater. It was assumed to be a slightly halophilic marine bacterium (optimal growth at 30‰ of salinity) by the researchers that described the species [ 58 , 59 ], who supposed that it was drawn into the saltern from the coastal environment [ 60 ]. No other work reports isolation of P ontimonas strains from MS or other hypersaline environments.…”
Section: Discussionmentioning
confidence: 99%
“…This genus includes only one species ( P. salivibrio ) and the only cultivable strain (CL-TW6) was isolated in Korea from a solar saltern pond showing salinity slightly higher than seawater. It was assumed to be a slightly halophilic marine bacterium (optimal growth at 30‰ of salinity) by the researchers that described the species [ 58 , 59 ], who supposed that it was drawn into the saltern from the coastal environment [ 60 ]. No other work reports isolation of P ontimonas strains from MS or other hypersaline environments.…”
Section: Discussionmentioning
confidence: 99%
“…The Pontimonas genus contains only one described strain, Pontimonas salivibrio strain CL-TW6 T , which was recently isolated from a coastal marine environment along with its virus and was hypothesized to occupy environments that experience significant stresses (57), such as Hamilton Harbour. The researchers concluded that its lytic virus was poorly adapted to replicate in this strain, since repeated attempts to sequence its genome were unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…In order to explore the distribution of HD-domain dNTPases in prokaryotes, we made use of the library of proteins from completely sequenced bacterial genomes (February 2018 version) described in 87 , and local implementations of the BLAST toolkit 88 , the HHpred system 89 , the UCSC Sequence Analysis and Alignment system 90 , PAUP ( https://paup.phylosolutions.com ), and MrBayes 3.2.7 91 . The library is formatted to contain protein accession, nucleotide accession, and full taxonomic distribution on each protein sequence definition line, making it possible to directly examine the distribution within genomes and taxons of any clade found within the library.…”
Section: Methodsmentioning
confidence: 99%